Kuuvan̳miut subsistence : traditional Eskimo life in the latter Twentieth Century - Anderson, Douglas D.; United States. National Park Service. ([Washington, D.C.?] : U.S. Dept. of the Interior, National Park Service, 1998)
"August 1998"--Colophon. Rev. ed. of: Kuuvan̳miit subsistence. 1977. Includes bibliographical references (p. 309-313) and index. Mode of access: Internet.